Universal women : filmmaking and institutional change in early Hollywood - Cooper, Mark Garrett (Women and film history international., 2010)
Between 1912 and 1919, the Universal Film Manufacturing Company first systematically supported and promoted women directors--crediting eleven women with directing at least 170 films--and then abruptly reversed that policy. In this trailblazing study, Mark Garrett Cooper approaches the phenomenon as a case study in how corporate movie studios interpret and act on institutional culture. In focusing on issues of institutional change, Cooper challenges interpretations that explain women's exile from the film industry as the inevitable result of a transhistorical sexism or as an effect of a broadly cultural revision of gendered work roles. Drawing on a range of historical and sociological approaches to studying corporate institutions, Cooper examines the relationship between institutional organization and aesthetic conventions during the formative years when women filmmakers such as Ruth Ann Baldwin, Cleo Madison, Ruth Stonehouse, Elise Jane Wilson, and Ida May Park directed films for Universal.